ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL MATEMATIKA SISWA KELAS XI SMK TAMTAMA KARANGANYAR TAHUN AJARAN 2013/2014 - Nurul Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2016)
An Error Analysis in SolvingMathematic Task to the Eleventh Grade Students of SMK Tamtama KaranganyarÂ in Academic Year 2013/2014. This studyaims to determinehow largea percentage ofthe errors, procedural errorsand errorsincomputingmath problemsto solvefundamentalintereststudentsof SMKTamtamaAK2. This was aqualitative descriptive studysubjectswere 42students drawnbypurposive sampling technique. The instrument used wasa test.Data Collection Technique uses ThinkOutlouds(TOL) technique. Data were analyzed usingdata analysis techniquesdeveloped byLexy J.Moleong: (1) review all thedata collected, (2) assess thestudents' workinmathematical problemsolvingfundamentalinterest, (3) to verify the data(conclusion). As forcheckingthe validity of thedata usingtriangulation techniques. The results ofthis study indicate that(1) the percentage oferrorswas11.43% with very low, (2) the percentageerrorof 12.38% standardwith very low, (3) the percentageerrorof 18.57% computationby categoryvery low. Suggestionsresearchers (1) for prospectiveteachers, may be able to preventand overcomethedifficultiesat least reducethe difficulties experiencedby students, (2) for teachers, provide trainingto students toperform calculations quickly andaccurately